1995
DOI: 10.1177/014920639502100108
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Cross-Situational-Consistency: A Confirmatory Factor Analytic Approach

Abstract: Numerous procedures have been suggested for investigating behaviors across situations for consistency versus situational specificity. It is proposed here that Confirmatory Factor Analysis (CFA) may provide an useful addition to these procedures. To illustrate the process, a CFA model based on simulated data is presented and tested. The results of this simulation are employed to make recommendations for conducting CFA to test for crosssituational consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Theoretical analysis was used to establish a priori model that comprised the observed variables, the unobserved variables, and theoretical correlations among the variables. Good fits between the theoretical correlations and the empirical correlations computed from empirical data would confirm the accuracies of the theoretical correlations and the usefulness of the priori model (Hemmelgarn et al, 1995). In this study, the observed variables are the indicators of VAO BIM climate and the unobserved variables are its dimensions.…”
Section: Analytic Strategysupporting
confidence: 65%
“…Theoretical analysis was used to establish a priori model that comprised the observed variables, the unobserved variables, and theoretical correlations among the variables. Good fits between the theoretical correlations and the empirical correlations computed from empirical data would confirm the accuracies of the theoretical correlations and the usefulness of the priori model (Hemmelgarn et al, 1995). In this study, the observed variables are the indicators of VAO BIM climate and the unobserved variables are its dimensions.…”
Section: Analytic Strategysupporting
confidence: 65%
“…The CFA is a statistical technique for verification of the factor structure of observed variables. It allows the testing of the hypotheses that there is a relationship between the observed variables and the corresponding latent constructs (Hemmelgarn et al ., 1995; Schreiber et al ., 2006; Strauss and Smith, 2009). In CFA the relationship patterns are hypothesized on basis of the theoretical knowledge or empirical research, or both in advance, which then is followed by the statistical hypothesis testing (Chan et al ., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The CFA is a statistical technique for verification of the factor structure of observed variables. It allows the testing of the hypotheses that there is a relationship between the observed variables and the corresponding latent constructs (Hemmelgarn et al, 1995;Schreiber et al, 2006;Strauss and Smith, 2009). In CFA the relationship patterns are hypothesized on basis of the theoretical knowledge or empirical research, or both in advance, which then is followed by the statistical hypothesis testing (Chan et al, 2007).The various factors that impact the use of CFA are the research hypothesis that is being tested, measurement instruments, sample size, multivariate normality, identification of parameters, missing data, outliers, or interpretation of the indices of model fit (Schumaker and Lomax, 1996).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…But traits only correlate with behavior across situations at r = +.30. Empirical results suggest methodological improvements could increase traits' predictive power if they are used to predict behavior in a specific-enough social context; if the social context from which the trait is inferred (previous context) and the social context that was being predicted (future context) are similar enough, then correlation coefficients rise above the modest mark of +.30, and traits become better predictors (Baird & Lucas, 2011;Hemmelgarn, James, Ladd, & Mitchell, 1995;Magnusson, 1976;Paunonen & Jackson, 1986;Van Mechelen, 2009).…”
mentioning
confidence: 99%